Efficacy of Intravenous Mesenchymal Stem Cells for Motor Recovery After Ischemic Stroke: A Neuroimaging Study. Issue 1 (29th September 2021) - Lee, Jungsoo; Chang, Won Hyuk; Chung, Jong-Won; Kim, Suk Jae; Kim, Soo-Kyoung; Lee, Jin Soo; Sohn, Sung-Il; Kim, Yun-Hee; Bang, Oh Young; ,
Abstract : Supplemental Digital Content is available in the text. Abstract : Background and Purpose: Stem cell–based therapy is a promising approach to repair brain damage after stroke. This study was conducted to investigate changes in neuroimaging measures using stem cell–based therapy in patients with ischemic stroke. Methods: In this prospective, open-label, randomized controlled trial with blinded outcome evaluation, patients with severe middle cerebral artery territory infarct were assigned to the autologous mesenchymal stem cell (MSC) treatment or control group. Of 54 patients who completed the intervention, 31 for the MSC and 13 for the control groups were included in this neuroimaging analysis. Motor function was assessed before the intervention and 90 days after randomization using the Fugl-Meyer assessment scale. Neuroimaging measures included fractional anisotropy values of the corticospinal tract and posterior limb of the internal capsule from diffusion tensor magnetic resonance imaging and strength of connectivity, efficiency, and density of the motor network from resting-state functional magnetic resonance imaging. Results: For motor function, the improvement ratio of the Fugl-Meyer assessment score was significantly higher in the MSC group compared with the control group. In neuroimaging, corticospinal tract and posterior limb of the internal capsule fractional anisotropy did not decrease in the MSC group but significantly decreased at 90 days after randomization in the control group. Interhemispheric connectivity and ipsilesional connectivity significantly increased in the MSC group. Change in interhemispheric connectivity showed a significant group difference. Conclusions: Stem cell–based therapy can protect corticospinal tract against degeneration and enhance positive changes in network reorganization to facilitate motor recovery after stroke. Registration: URL: https://www.clinicaltrials.gov ; Unique identifier: NCT01716481.